Analysis of Three Armed Signal Intersections With MKJI 1997 Method - Amar Mufhidin; Nurohman Nurohman; Muhammad Isradi; Hermawan Hermawan; Rifai Rifai (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734, 2022)
Bekasi Regency is a regency in West Java Province with a population of ± 3,899,00 Million People (Based on Statistics Indonesia, 2020). Diponegoro Highway – Setia Mekar Street Bekasi Regency is access to the main road to the city border, besides that access to residential locations, schools, and many companies which makes vehicle traffic especially during rush hour more congested by the activities on the side of the road such as slow vehicle, the ups and downs of passengers, so vehicles that stop causing long vehicle queues. From the results of the analysis, the results of signalized intersection can be obtained on the Diponegoro Highway Setia Mekar Street Bekasi Regency. It is known that the greatest Degree of Saturation is in the Northen approach which is 1,12 with a average intersection delay is 99,21 seconds/smp. Furthermore, Alternative solutions is carried out by changing side obstacles from 0,94 to 0,95 and recycling time intersection, resulting in a decrease in the average intersection delay and improvement of indoporlen intersection services